Focus: A Usable & Effective Approach to OLED Display Power Management - TAN, Kiat Wee (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we present the design and implementation of Focus, a system for effectively and efficiently reducing power consumption of OLED displays on smartphones. These displays, while becoming exceedingly common still consume significant power. The key idea of Focus is that we use the notion of saliency to save display power by dimming portions of the applications that are less important to the user. We envision Focus being especially useful during low battery situations when usability is less important than power savings. We tested Focus using 15 applications running on a Samsung Galaxy S III and show that it saves, on average, between 23 to 34% of the OLED display power with little impact on task completion times. Finally, we present the results of a user study, involving 30 participants that shows that Focus, even with its dimming behaviour, is still quite usable.